Coprological Investigation of helminths parasitic infestations of Buffalo at haor and hilly bordered areas of Sylhet district in Bangladesh: Helminthes of Buffalo - Siddiqui, Prof. Dr. Md. Saiful Islam; Mahtab, Jannatun Nayeem Hossain; Mamun, Mohammad Abdullah Al; Islam, Saiful; Hasan, Rakibul; Islam, MD. Nazrul; Begum, Sultana; Nasrin, Farhana; Paul, Tapan Kanti; Amin, S. M. Nurul (Faculty of Veterinary Medicine Universitas Brawijaya, 2025)
This study was designed and conducted with the aims to investigate the status of the parasitic infestations of buffaloes rearing in the Haor and bordered hilly areas of Sylhet district of Bangladesh as the ecology and the geographical facts are facilitating favorable conditions for parasites. Based on zoo-geography of different haor and hilly areas belongs to five Upazilla of Sylhet district were selected as study areas. A total 200 (40 samples from each Upazilla) fecal samples from randomly selected study buffalo based on considering survey findings, age, sex and seasons were collected and tested using direct smear method, floatation and McMaster egg counting techniques. Fascioliasis was the most prevalent (20.5%) parasitic infection, with an overall prevalence of 84.5%. The level of parasite infection varied throughout the five haor and adjacent areas of Sylhet; Jaintapur had the highest level (85%) and Zakiganj the lowest (65%). Out of the three helminth categories, Guwainghat had the highest prevalence of treamtaode (31.25%) and cestode (28.12%), while Kanaighat had the highest (51.72%) prevalence of nematode infection. Fascioliasis was most prevalent (46%) in adult buffaloes, while toxocariasis was highest in buffalo calves. Comparatively higher parasitic infection was seen in wet season (80.82%), followed by 61.25% in dry season. It is concluded that, prevalence of helminthes parasite are much more higher in buffaloes in the haor and bordered hilly areas in Sylhet due to zoo-geographical facts, which to be seriously considered by the related authority and would formulate a specific helminthes control strategic plan for haor areas.